ENVIRONMENTAL HEALTH RISK ASSESSMENT OF GROUNDWATER NITRATE AND NITRITE EXPOSURE AMONG FARMERS IN COASTAL AREA OF REMBANG, CENTRAL JAVA, INDONESIA - Septiria Irawati; Cita Fitria Putri (Fakultas Kesehatan Masyarakat Indonesia, 2026)
Background: The increasing use of fertilizers and pesticides in agricultural areas maycontaminate groundwater with nitrate and nitrite, posing health risks. Objective: This study aimed to assess the health risk from nitrate and nitrite exposure through groundwater consumption among farmers in the coastal area of Rembang, Central Java. Methods: A crosssectional study was conducted in Gunungsari Village, Kaliori Subdistrict. Groundwater samples from seven households were analyzed using spectrophotometry and compared with national drinking water standards. Respondent characteristics were obtained through questionnaires, and Chronic Daily Intake (CDI) and Risk Quotient (RQ) were calculated for children and adults. Results: This study showed that nitrate concentrations were below the limit (10 mg/L), while one sample exceeded the nitrite standard (8 mg/L vs. 1 mg/L). CDI values ranged from 0.017–0.021 mg/kg/day in adults and 0.082 mg/kg/day in a child, all with RQ<1. Conclusion: Groundwater samples in the agricultural area of Rembang generally indicated no immediate health threat of nitrate and nitrite contamination. Suggestion: Continuous monitoring and community education are needed to prevent chronic exposure and potential long-term effects from endogenous nitrosation